MOLDS PRODUCTION PROGRESS MAPPING – A VISUAL MANAGEMENT TOOL FOR THE INDUSTRY 4.0 - Diogo Pina Jorge; Paulo Peças (Revista Produção e Desenvolvimento, 2018)
The planning of injection molds production is a complex task where the classic planning approaches has proven limitations because of the following particular characteristics: the mold expands in a myriad of components for production; the “one-of-a-kind” type of production and recurrent mold design changes asked by the customer. To overcome this challenge a methodology to Molds Production progress Mapping is proposed (MPM). The methodology was built on the authors experience in collaborating with mold making companies, on the principles of lean manufacturing and visual management (VM) and also have in mind the trend towards production digitalization to be aligned with Industry 4.0 evolution. As a VM tool to support molds production planning, the MPM shows the instant progress of each mold, the deviation from planning and the remaining time for the due date.  The user has “only” to input the mold’s components critic level and the relative weight of each production process in the total time; it also requires that the production process are armed with sensors and the production task are digitalized and compiled in the information management system. The MPM can also be used in other complex production systems.